Interaction between PLA2R1 and HLA‐DQA1 variants contributes to the increased genetic susceptibility to membranous nephropathy in Western China. Issue 9 (29th April 2019) - Wang, Wei; Fan, Shulei; Li, Guisen; Wang, Amanda Y; Hong, Daqing; Zhong, Xiang; Wang, Li
ABSTRACT: Aim: Recent studies showed that single nucleotide polymorphisms (SNP) within the phospholipase A2 receptor (PLA2R1) and human leukocyte antigen complex class II HLA‐DQα‐chain 1 (HLA‐DQA1) genes were associated with the susceptibility to patients with primary membranous nephropathy (PMN). However, the results of previous research have not been always consistent. Methods: We performed a case–control study including 314 patients with PMN and 354 healthy subjects in Western China. Eight SNP in PLA2R1 and one SNP in HLA ‐DQA1 were genotyped and association between PLA2R1 and HLA‐DQA1 was investigated. One hundred and twenty patients were detected anti‐PLA2R antibodies to analyze the association between genotype and anti‐PLA2R antibody. Results: We found A allele of rs2715918 (odds ratio (OR) = 1.66, corrected P values ( Pc ) = 7.9 × 10 −3 ), A allele of rs4665143 (OR = 1.76, Pc  = 2.7 × 10 −6 ) and A allele of rs2187668 (OR = 3.29, Pc  = 8.0 × 10 −11 ) were associated with PMN. Susceptibility of PMN was significantly increased with rs2715918 in dominant model (OR = 1.624, Pc = 5.0 × 10−2 ), rs4665143 in recessive model (OR = 2.134, Pc  = 1.4 × 10 −4 ) and rs2187668 in dominant model (OR = 3.961, Pc  = 4.1 × 10 −11 ). The haplotype ATAC of rs2715918, rs6757188, rs4665143, rs3749119 was associated with the high risk of PMN (OR = 1.453, P  = 3.0 × 10 −4 ). Interaction of rs2715918 GA/AA, rs4665143 GA/AA and rs2187668 GA/AA could significantly increase the 10.61‐fold higher risk for the development of PMN (OR = 10.61, P  = 4.0 × 10 −10 ). Patients who carried with risk genotypes for both HLA‐DQA1 and PLA2R1 (87.8%) had antibodies positivity. However, patients who carried low‐risk genotypes (41.6%) had antibodies positivity ( P  = 0.001). Conclusion: There are some differences in PLA2R1 distributions in PMN patients between previous literature and our study. Our results showed that interactions between PLA2R1 and HLA‐DQA1 alleles increased genetic susceptibility to PMN in Western China. SUMMARY AT A GLANCE: This study points to heterogeneity in genetic risk for the development of primary membranous nephropathy (IMN) among different racial groups. Investigators from Western China found single nucleotide polymorphisms (SNP) that were associated with IMN to be different from those observed in other racial groups. As a first study to perform SNP–SNP interaction analysis, the authors showed that the combination of risk genotypes of 3 SNPs (rs2715918 GA/AA, rs4665134 GA/AA and rs2187668 GA/AA) conferred a 10.61‐fold higher risk of IMN.